Tumor odontogênico queratocístico: revisão de literatura - Jardim, Ellen Cristina Gaetti [UNESP]; Pereira, Cassiano Costa Silva [UNESP]; Carvalho, Abrahão Cavalcante Gomes de Souza [UNESP]; Gealh, Walter Cristiano [UNESP]; Shinohara, Elio Hitoshi [UNESP] (My University, 2011)
The odontogenic keratocyst is called keratocyst odontogenic tumor (TOQ), due to its features compatible with neoplasms, such as its high recurrence rate and mechanism of growth. Although its etiology has unknown, the origin seems to be connected with dental lamina remaining. This entity is generally benign, with slow progression, asymptomatic, and among the odontogenic tumors, its prevalence is high. It affects mainly males, with predilection for the posterior mandible, while in most cases associated with an impacted tooth. Radiographically, this lesion is unilocular. Histological features are stratified epithelial basal cells with hyperchromatic paraqueratinizado. Treatment ranges from conservative to radical interventions. As a result of the controversy as TOQ tumor entity, the present work is a literature review of current findings, emphasizing its intrinsic features to contribute to developments in the study of this new entity.

O queratocisto odontogênico é denominado tumor odontogênico queratocístico (TOQ), graças a suas características compatíveis com neoplasmas, como sua alta taxa de recorrência e mecanismo de crescimento diferenciado. Embora ainda tenha etiologia desconhecida, acredita-se que sua origem esteja relacionada com os remanescentes da lâmina dentária. Tal entidade é de natureza benigna, com evolução lenta, assintomática e, dentre os tumores odontogênicos, apresenta alta prevalência. Acomete principalmente o sexo masculino, com predileção pela região posterior da mandíbula, estando na maioria dos casos associado a um dente incluso. Radiograficamente, essa lesão é unilocular. Histologicamente, apresenta revestimento epitelial do tipo estratificado paraqueratinizado com células basais hipercromáticas. O tratamento varia desde intervenções conservadoras ao radical. Em decorrência das controvérsias do TOQ como entidade tumoral, o presente trabalho faz uma revisão de literatura dos achados atuais, enfatizando características intrínsecas deste, a fim de contribuir com a evolução no estudo dessa nova entidade.
Keratocyst odontogenic tumor: review of literature
Keywords: Odontogenic cysts; Odontogenic tumors; Jaw cysts; Cistos odontogênicos; Tumores odontogênicos; Cistos maxilomandibulares